MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM SOLVING BERBASIS EKSPERIMEN DALAM PEMBELAJARAN FISIKA - Suherman . (Jurnal Pendidikan Fisika, 2013)
The objective in this study to improve students learning outcomes by using learning model problem solving based experiments in learningphysics. The subjects were students of class XI IA-1 SMAN 1 Stabat totaling 38 people, consisting of 10 men and 28 women. Student learning outcomes inthe cognitive domain in the first cycle the average values posttest obtained 72.95 with N-gain of 37% including the category, the second cycle increasedto 77.30 with N-gain of 43% including the medium category. The number ofstudents who pass the study increased from 63.16% to 86.84% first cycle tothe second cycle. Student learning outcomes in the psychomotor domain ofthe first cycle obtained an average value of 72.11 including sufficient criteriaand the second cycle becomes 77.54 including both criteria. Classicalcompleteness in the first cycle of 52.63% and the second cycle becomes 89.47%. Student learning outcomes in the affective domain, the averagevalues obtained 64.47 including sufficient criterion in the first cycle and thesecond cycle becomes 75.09 including both criteria. Completeness in the firstcycle of 44.74% and the second cycle becomes 94.74%. Conclusion: there isan increase in student learning outcomes in the cognitive, psychomotordomain and affective domain by using learning problem solving basedexperiment.